2019
DOI: 10.1080/0284186x.2019.1695062
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age on the efficacy of immune checkpoint inhibitors in advanced cancers: a systematic review and meta-analysis

Abstract: Background: Immune checkpoint inhibitors (ICIs) represent a paradigm shift in the development of cancer treatment. However, it remains to be clarified whether the benefits that they confer differ according to patient age. We conducted a systematic review and meta-analysis to assess age differences in the benefits of ICI treatment. Methods: We systematically searched the PubMed database for randomised controlled trials of ICIs, including PD-1, PD-L1 and CTLA-4 inhibitors across multiple cancer types, such as me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 63 publications
2
22
0
1
Order By: Relevance
“…Age affects host immunity and therefore could affect the effectiveness of ICI treatment. Although some meta-analyses have found that the therapeutic effect of ICI was independent of age ( 21 , 22 , 43 – 45 ), these meta-analyses mainly focused on ICI monotherapy or total cancer treatment and did not specifically study the influence of age on ICI combined with other treatments in the context of NSCLC. To the best of our knowledge, this is the first meta-analysis to investigate the impact of age on the efficacy of ICI-based combination therapy vs. non-ICI therapy in NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age affects host immunity and therefore could affect the effectiveness of ICI treatment. Although some meta-analyses have found that the therapeutic effect of ICI was independent of age ( 21 , 22 , 43 – 45 ), these meta-analyses mainly focused on ICI monotherapy or total cancer treatment and did not specifically study the influence of age on ICI combined with other treatments in the context of NSCLC. To the best of our knowledge, this is the first meta-analysis to investigate the impact of age on the efficacy of ICI-based combination therapy vs. non-ICI therapy in NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the preclinical data mentioned above, it is speculated that older patients obtain limited benefits from ICI treatment compared to younger patients. However, some studies have reported that the benefit of ICI treatment is independent of age (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Zwar liegt z. B. eine größere Metaanalyse zur Wirkung von Checkpoint-Inhibitoren bei verschiedenen Tumoren und die potenzielle Beeinflussung des Effekts durch das Alter vor, bei denen für Anti-PD-1-und Anti-PD-L1-Therapie eine ähnliche Wirkung bei jüngeren wie älteren Patienten und eine allerdings nicht signifikante schwächere Wirkung bei Älteren für CTLA-4-Inhibitoren gezeigt wurde [12], die Rolle von Mikronährstoffen war dabei aber nicht berücksichtigt worden. Außerdem waren Patienten über 65 Jahren in den zugrundeliegenden Studien ausgeschlossen, die Hauptzielgruppe ist also gar nicht abgebildet worden.…”
Section: Mikronährstoffe In Der Immunresponseunclassified
“…PD-L1 (Atezolizumab) inhibitors had comparable efficacy in adults with metastatic cancer in people older than 65 years of age [36]. Furthermore, two large meta-analysis investing the impact of age on the efficacy of ICIs used for treatment of multiple metastatic cancer types showed no difference between young and older patients (cut off = 65 years) [40,41]. In addition, a systematic review of 23 randomized controlled trials involving 9322 men (67.9%) and 4399 women (32.1%) with advanced cancer receiving ICIs showed no statistically significant impact of patients' gender on the efficacy of ICIs measuring overall survival as the primary outcome [42].…”
Section: Immune Checkpoint Inhibitors (Ici) I Proof Of Efficacy and Smentioning
confidence: 99%